Russia's War in Ukraine: Consequences for European countries' businesses and economies - Anatolijs Prohorovs (Journal of Risk and Financial Management, 2022)
Companies and countries have needed to adapt their activities to the consequences of the Russian war in Ukraine. The analysis in this article shows that both the Russian war in Ukraine and the subsequent trade restrictions have become a powerful trigger, significantly increasing the level of inflation and exacerbating the existing issues of economies. As a result, the confrontation between the West and Russia has greatly escalated, which will have a long-term, large-scale negative impact on most European companies and economies. There could also be a lasting restructuring of world trade. The article notes that not only the end date of the war in Ukraine may be important for business and economies, but also which of the trade and financial restrictions can be lifted from Russia, and when. The article also makes recommendations that may help company leaders plan, in a timelier and more accurate fashion, the changes necessary to maintain company sustainability.
Keywords: 650; Europe; business; companies; consequences; economy; embargo; war in Ukraine